VARIASI KONSENTRASI JELLY POWDER PADA PEMBUATAN JELLY DRINK BROKOLI (Brassica oleracea var. Italica) - Widjaja, Willy Pranata; Cahyadi, Wisnu; Suliasih, Neneng; Ridzkiani, Hana Putri (Department of Food Technology, Universitas Pasundan, Bandung, 2025)
This study investigates the effect of jelly powder concentration on the quality characteristics of broccoli jelly drink (Brassica oleracea var. Italica). A randomized block design with four levels of jelly powder (0.6%, 0.7%, 0.8%, and 0.9%) was applied. Parameters analyzed included pH, vitamin C content, viscosity, sensory attributes (color, aroma, taste, suction power), and antioxidant activity (IC₅₀) for the best treatment. Results showed significant effects (p < 0.05) of jelly powder concentration on all variables. Higher concentrations increased viscosity but decreased pH, vitamin C stability, and sensory acceptability. The 0.6% concentration was selected as optimal, showing balanced pH (4.78), viscosity (198.83 cP), vitamin C (131.67 mg/100 g), and favorable sensory scores. However, its antioxidant activity was classified as very weak (IC₅₀ = 4667.89 ppm). Optimization is required to enhance functional benefits.